Économiste et développement durable : de la professionnalité aux métiers - Catherine Figuière; Michel Rocca (Développement Durable et Territoires)
Jobs requiring skills which integrate some dimensions of sustainable development are increasingly numerous, even if their description is not always clear. This paper proposes primarily to identify newly-created jobs from traditional jobs integrating new issues in their description. The jobs offered to economists clearly belong to the second category. Then, based on an experiment carried out at Grenoble University, this paper aims at stressing the need for training including on the one hand, courses “about sustainable development” and on the other, proficiency in using some transversal tools of economics and management, such as organisational change management. This proficiency is indeed imposed by the large variety of the professional positions on offer in this field.